STUDY OF THE MECHANICAL PROPERTIES OF POLYMER FILMS FROM LATEX POLYMERS CORE / SHELL OBTAINED IN MICRO EMULSION POLYMERIZATION AND EMULSION - Pucca P., M. (2013)
In this paper the synthesis of core-shell (polystyrene / polyacrylate butyl ) using a rigid polymers such as polystyrene core with soft shell as butyl polyacrylate (and vice versa ) in the proportions 40/60 and 60/40 is reported, obtained by emulsion polymerization and microemulsion . The mechanical properties of the solid material obtained was studied , as well as of the films formed by the deposition of latex on a flat surface and dried at 30 ° C. The films were prepared by polymer core / shell obtained in microemulsion , had higher values ​​of tensile modulus and tensile strength than the films prepared using polymer core / shell emulsion obtained .